Neutrophil Percentage-to-Albumin Ratio and Risk of Mortality in Patients on Peritoneal Dialysis - Yu Y; Zhong Z; Yang W; Yu J; Li J; Guo X; Chen J; Mao H; Li Z (Dove Medical Press, 2023)
Yi Yu,1,2,* Zhong Zhong,1,2,* Wenzhuo Yang,1,2 Jianwen Yu,1,2 Jianbo Li,1,2 Xingdi Guo,1,2 Jiasi Chen,3 Haiping Mao,1,2 Zhijian Li1,2 1Department of Nephrology, The First Affiliated Hospital, Sun Yat-sen University, Guangzhou, 510080, People's Republic of China; 2NHC Key Laboratory of Clinical Nephrology (Sun Yat-Sen University) and Guangdong Provincial Key Laboratory of Nephrology, Guangzhou, 510080, People's Republic of China; 3Department of Nephrology, The First Affiliated Hospital, Guangzhou Medical University, Guangzhou, 510120, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhijian Li, Department of Nephrology, The First Affiliated Hospital, Sun Yat-Sen University, 58th Zhongshan Road II, Guangzhou, 510080, People's Republic of China, Tel +8620 87335811, Fax +8620 87755766, Email lizhjian@mail.sysu.edu.cnBackground: Neutrophil percentage-to-albumin ratio (NPAR), a new inflammatory marker, has been shown to be associated with poor prognosis in patients with cardiovascular disease. However, limited evidence is available for its role in peritoneal dialysis (PD) patients. Our study aimed at investigating the prognostic value of NPAR for mortality in PD patients.Patients and Methods: This was a single center retrospective cohort study. A total of 1966 PD patients were enrolled in our study from January 2006 to December 2016 and were followed up until December 2021. Patients were stratified into tertiles according to baseline NPAR levels. The associations between NPAR levels with all-cause and cardiovascular mortality were estimated using Cox proportional hazards models. Receiver operating characteristic (ROC) analysis was performed to compare the mortality predictive values of NPAR and other known biomarkers, such as NLR (neutrophil-to-lymphocyte ratio), PLR (platelet-to-lymphocyte ratio), LHR (low-density lipoprotein cholesterol-to-high-density lipoprotein cholesterol ratio) and MLR (monocyte-to-lymphocyte ratio).Results: During a median follow-up of 48.1 months, 503 (25.6%) patients died, in which cardiovascular disease (CVD) death dominated 50.3%. Multivariate Cox regression analysis revealed that the highest NPAR tertile was significantly associated with a higher risk of all-cause and cardiovascular mortality (HR 1.51, 95% CI 1.14- 1.98; HR 1.57, 95% CI 1.07- 2.31; respectively) compared with tertile 1. The AUC values of NPAR were 0.62 (95% CI 0.60- 0.65, P < 0.001) for all-cause mortality and 0.61 (95% CI 0.57- 0.65, P < 0.001) for cardiovascular mortality.Conclusion: Our study showed that higher NPAR levels were independently associated with increased risk of all-cause and cardiovascular mortality in PD patients. Notably, our results demonstrated that NPAR exhibited superior predictive value for mortality compared to NLR, PLR, MLR, and LHR.Keywords: peritoneal dialysis, neutrophil percentage-to-albumin ratio, mortality, inflammation